Donatella della Porta, Lorenzo Cini y César Guzmán-Concha. Contesting Higher Education. Student Movements against Neoliberal Universitie - Seia, Guadalupe Andrea (CIAN-Revista de Historia de las Universidades, 2020)
Este artículo reseña: Donatella della Porta, Lorenzo Cini y César Guzmán-Concha. Contesting Higher Education. Student Movements against Neoliberal Universities. Bristol: Bristol University Press, 2020, 230 pp.